Mesoporous Silica Nanomaterials: Versatile Nanocarriers for Cancer Theranostics and Drug and Gene Delivery - Kesse, Samuel; Boakye-Yiadom, Kofi Oti; Ochete, Belynda Owoya; Opoku-Damoah, Yaw; Akhtar, Fahad; Filli, Mensura Sied; Asim Farooq, Muhammad; Aquib, Md; Maviah Mily, Bazezy Joelle; Murtaza, Ghulam; Wang, Bo (Pharmaceutics, 2019)
Mesoporous silica nanomaterials (MSNs) have made remarkable achievements and are being thought of by researchers as materials that can be used to effect great change in cancer therapies, gene delivery, and drug delivery because of their optically transparent properties, flexible size, functional surface, low toxicity profile, and very good drug loading competence. Mesoporous silica nanoparticles (MSNPs) show a very high loading capacity for therapeutic agents. It is well known that cancer is one of the most severe known medical conditions, characterized by cells that grow and spread rapidly. Thus, curtailing cancer is one of the greatest current challenges for scientists. Nanotechnology is an evolving field of study, encompassing medicine, engineering, and science, and it has evolved over the years with respect to cancer therapy. This review outlines the applications of mesoporous nanomaterials in the field of cancer theranostics, as well as drug and gene delivery. MSNs employed as therapeutic agents, as well as their importance and future prospects in the ensuing generation of cancer theranostics and drug and therapeutic gene delivery, are discussed herein. Thus, the use of mesoporous silica nanomaterials can be seen as using one stone to kill three birds.